Variability of Intra–D Ring Azimuthal Magnetic Field Profiles Observed on Cassini's Proximal Periapsis Passes. Issue 1 (30th January 2019) - Provan, G.; Cowley, S. W. H.; Bunce, E. J.; Bradley, T. J.; Hunt, G. J.; Cao, H.; Dougherty, M. K.
Abstract: We overview the properties of the azimuthal magnetic fields observed during the periapsis passes of the final 23 orbits of the Cassini spacecraft, including the partial orbit at end of mission, on near equatorial field lines passing inside of Saturn's D ring. The signatures are variable in form and amplitude, though generally approximately symmetric about the point where the spacecraft trajectory lies tangent to a flux shell, corresponding to where the ionospheric field line feet map closest to the equator, consistent with the effect of interhemispheric field‐aligned currents. The perturbations usually begin and end near symmetrically at some point on field lines threading the D ring and extend into the interior region, but in no case do they clearly extend outward onto field lines passing through the C ring. About 35% of cases display a 20‐40 nT single positive central field peak indicative of southward field‐aligned current flow, while a further 30% display two or three weaker 10‐20 nT positive peaks indicative of multiple sheets of northward and southward current. Significant smaller‐scale >5 nT peak‐to‐peak field fluctuations are commonly superposed. A further 20% of cases exhibit unique profiles within the data set, including two with 20‐30 nT negative fields and two with only <10 nT fluctuating fields. The variable nature of the signatures is not connected with the pass altitude, local time, planetary period oscillation phase, or D68 ringlet phase but may relate to variable structured thermospheric winds and/or ionospheric conductivities that suggest a significant dynamical role for D ring‐atmosphere interactions. Key Points: Azimuthal magnetic fields observed on Saturn's intra‐D ring (IDR) field lines exhibit a range of profiles on the 23 Cassini proximal passes One, two, or three near‐symmetrical positive peaks 10‐40 nT are typical, but two passes have 20‐30 nT negative peaks and two <10 nT fields Variable IDR field signatures are not organized by periapsis radius, local time, planetary period oscillation phase, or D68 ringlet phase